Limbic Serotonergic Plasticity Contributes to the Compensation of Apathy in Early Parkinson's Disease. Issue 6 (3rd March 2022) - Prange, Stéphane; Metereau, Elise; Maillet, Audrey; Klinger, Hélène; Schmitt, Emmanuelle; Lhommée, Eugénie; Bichon, Amélie; Lancelot, Sophie; Meoni, Sara; Broussolle, Emmanuel; Castrioto, Anna; Tremblay, Léon; et al.
Abstract: Background: De novo Parkinson's disease (PD) patients with apathy exhibit prominent limbic serotonergic dysfunction and microstructural disarray. Whether this distinctive lesion profile at diagnosis entails different prognosis remains unknown. Objectives: To investigate the progression of dopaminergic and serotonergic dysfunction and their relation to motor and nonmotor impairment in PD patients with or without apathy at diagnosis. Methods: Thirteen de novo apathetic and 13 nonapathetic PD patients were recruited in a longitudinal double‐tracer positron emission tomography cohort study. We quantified the progression of presynaptic dopaminergic and serotonergic pathology using [ 11 C]PE2I for dopamine transporter and [ 11 C]DASB for serotonin transporter at baseline and 3 to 5 years later, using linear mixed‐effect models and mediation analysis to compare the longitudinal evolution between groups for clinical impairment and region‐of‐interest‐based analysis. Results: After the initiation of dopamine replacement therapy, apathy, depression, and anxiety improved at follow‐up in patients with apathy at diagnosis (n = 10) to the level of patients without apathy (n = 11). Patients had similar progression of motor impairment, whereas mild impulsive behaviors developed in both groups. Striato‐pallidal and mesocorticolimbic presynaptic dopaminergic loss progressed similarly in both groups, as did serotonergic pathology in the putamen, caudate nucleus, and pallidum. Contrastingly, serotonergic innervation selectively increased in the ventral striatum and anterior cingulate cortex in apathetic patients, contributing to the reversal of apathy besides dopamine replacement therapy. Conclusion: Patients suffering from apathy at diagnosis exhibit compensatory changes in limbic serotonergic innervation within 5 years of diagnosis, with promising evidence that serotonergic plasticity contributes to the reversal of apathy. The relationship between serotonergic plasticity and dopaminergic treatments warrants further longitudinal investigations. © 2022 International Parkinson and Movement Disorder Society